Epidemiology of Multi-Drug Resistant Organisms in a Teaching Hospital in Oman: A One-Year Hospital-Based Study - Abdullah Balkhair; Yahya M. Al-Farsi; Zakariya Al-Muharrmi; Raiya Al-Rashdi; Mansoor Al-Jabri; Fatma Neilson; Sara S. Al-Adawi; Marah El-Beeli; Samir Al-Adawi (The Scientific World Journal)
Background. Antimicrobial resistance is increasingly recognized as a global challenge. A few studies have emerged on epidemiology of multidrug resistant organisms in tertiary care settings in the Arabian Gulf. Aim. To describe the epidemiology of multi-drug resistant organisms (MDRO) at Sultan Qaboos University Hospital, a tertiary hospital in Oman. Methods. A retrospective review of MDRO records has been conducted throughout the period from January 2012 till December 2012. Organisms were identified and tested by an automated identification and susceptibility system, and the antibiotic susceptibility testing was confirmed by the disk diffusion method. Results. Out of the total of 29,245 admissions, there have been 315 patients registered as MDRO patients giving an overall prevalence rate of 10.8 (95% CI 9.3, 12.4) MDRO cases per 1000 admissions. In addition, the prevalence rate of MDRO isolates was 11.2 (95% CI 9.7, 12.9) per 1000 admissions. Overall, increasing trends in prevalence rates of MDRO patients and MDRO isolates were observed throughout the study period. Conclusion. Antimicrobial resistance is an emerging challenge in Oman. Continuous monitoring of antimicrobial susceptibility and strict adherence to infection prevention guidelines are essential to prevent proliferation of MDRO. Along such quest, stringent antibiotic prescription guidelines are needed in the country.